AN EXPLORATORY STUDY ON THE IN- STORE ENVIRONMENTAL ELEMENTS AS A NON-VERBAL COMMUNICATION INFLUENCER ON THE PURCHASE INTENTION OF THE CONSUMERS TOWARDS NILGIRI’S SUPER MARKETS IN CHENNAI CITY - Ramprabha, K.; Gnanasundari, M.; Kumar, S.Nithish (International Journal of Psychosocial Rehabilitation, 2020)
The Indian retail marketplaceincorporates a vivaciousamalgamation of challengingshoppers, increasingechelons of consumption patterns and a risingpopulace base. The purchasingpronouncementof a shopperpasses through various levels, which are perpetually influenced by behavioural forces.It’sessential for the retailers to form their retail store environment as enjoyable as possible so as to gratify their shoppers’desires and deliver them with agratifying experience.Once customers are inside a retail store, variouscomponentshave an emotional impacton their perceptions, namely; lighting, flooring, aroma, music, colours, textures, wall displays etc. Zentes, Morschett, and Schramm-Klein (2007) advocate that the shoppers experience the retail store atmosphere initially through their sensory channels such as sight, sound, scent, touch and taste.Next, purchase intention is the liking of the shopper to purchase the product or service.Many factors may have an effect on the consumer’s purchase intention while selecting the product and the ultimate buying decision depends on consumers’ intention with large external factors (Keller, 2001).Siu and Hua (2001) specified that physical look of a retail store has the utmost impact on the overall service quality, increased customer retention and higher future consumption, respectively.The study conducted by Satish and Peter (2004) elucidates that knowledge about the product by the patron plays an integral role throughout the product purchase decision. Other studies like Rao and Monroe (1988) argued that knowledge of the product is the major factor in product purchasing decision. Product packaging in which one thought is simple outlook and second thought is to prepare attractive packaging. These factors are also very important and have influenced on consumer purchase intention (Ann, 2008). Another study of Fung et al., (2004) exposed that shoppers’ feelings are attached with design and packaging. This research paper has been envisioned to seem into the collective influence of the in-store retail environmental factors such as interior and exterior store atmospherics, store layout, depth and width of merchandise, store staff, price and promotional activities, social status and customer service that make an effect on the customers and have an influence on their purchase intentions. In today’s society consumers are experiencing more time pressures and expect a break out from the hectic and stressful days.A conceptual framework is designed based on the literature. The framework provides the inspiration for the study. To achieve the objective, the research instrument is developed and validated. The research instrument executed is questionnaire which is self-structured. The research is targeted towards both shopper genders who shop at supermarkets. The supermarkets included Nilgiri’s supermarkets. The area of sampling included Purasaiwakam and Anna Nagar, Chennai. The primary data was collected using mall intercept method. The sample size is 300. 150 respondents were selected from each area respectively. The respondents were selected based on judgement and convenience. Data collection was done by visiting the stores multiple times at various timings incorporating more and less crowded conditions. The reliability of the tool was checked and the alpha values were also obtained. The research instrument is then factor analysed and the validity is checked using Confirmatory Factor Analysis. Structure Equation Modelling is used to test the hypothesis.The results show that the customers who shop at supermarkets in Chennai city, India, have high expectations and are influenced towards the retail attributes of the stores. This influence on the other hand has an impact on their purchase intentions. The major intent of conducting this research was to identify the impact of atmospheric variables on theconsumer purchase intention in the Nilgri’s Supermarkets. Purchase intention is incongruent. Store ambience influences the customers greatly and much needs to be done to enhance the customers’ shopping experience. It is essential for the retailer to concentrate on the variety and quality of the products which calls for a good collection of brands and products. Consumers high on convince ability are prone to bump into sales situations thatcould end with them making unwanted purchases. Salespersons who encounter highlyconvincible consumers often have little incentive to not take advantage of the tendency.The managers can ensure and motivate thesalesperson for better results.In general, managersneed to look beyond store format in order to become more successful and to be able toprovide what the consumers want so that they become loyal customers.